ANALISIS KEMAMPUAN PEMECAHAN MASALAH BERDASARKAN GENDER PADA MAHASISWA KELAS STATISTIK - Mitra Permata Ayu; Yemi Maria Bouk; Maria Wilda Malo; Alexander Tallu Popo (Universitas Muhammadiyah Surabaya, 2024)
Problem solving ability is a skill that every student must have. This study aims to describe, analyze the problem solving ability of students based on gender with Polya stages. The subjects in this study were 30 third semester Informatics Engineering students consisting of 15 students (male) and 15 students (female). The data instruments used are tests and interviews. The results showed that the ability to solve problems in the high category of the female gender was better than the male gender; the ability to solve with the medium category of the male gender was better than the female gender and the ability to solve problems in the low category had the same number between the same female and male gender. This is because the subject has not fully understood the basic concepts of the material of statistical data centering measures. By maximizing learning with the right method and repetitive problem exercises, it can help hone students' problem solving skills, especially in the material of statistical data concentration measures. Keywords: problem solving, polya, gender